Experimental Study on Failure Law and Mechanism of Red Sandstone under Ultrasonic Vibration Excitation - Jiyao Wang; Xufeng Wang; Xuyang Chen; Liang Chen; Zhanbiao Yang; Zechao Chang; Lei Zhang; Zhijun Niu (Geofluids)
Rock breakage is inevitable for creating openings in underground engineering operations. Ultrasonic vibration has been attracting extensive attention for such a practice considering its outstanding performance in rock breakage. In order to understand the fundamental failure mechanism of rocks subjected to ultrasonic vibrations, based on P-wave monitoring and the direct current electric method, we captured the evolution of the failure process of the red sandstone. In addition, we fundamentally analyse the failure mechanisms of the red sandstone using numerical simulation and microscopy scans. It was found that extensive fractures were initiated due to the ultrasonic vibration and the fractures propagated downwards forming a conical shape. The apparent resistivity became as high as 320000 Ω being 16 times the initial resistivity. The fracture propagated downwards as deep as 41 mm. The maximum damage parameter on the testing sample could be as high as 0.68, and it completely failed after 140 s of ultrasonic vibration duration. As a result of numerical simulation, it was found that the microfractures and pores in the testing sample were activated due to the stress wave resulting from the ultrasonic vibration leading to the fracture propagation and eventually complete failure. Through comparing the performance of uniaxial compressive loading and ultrasonic vibration techniques in rock damage, it was concluded the latter has a much higher capacity and competence in rock breakage.